Carbamazepine and its metabolites in epileptic patients - Ebrahim, Osman (Division of Clinical Pharmacology, 2018)
Carbamazepine is a drug which is now widely used for the treatment of both generalised epilepsy (tonic-clonic seizures) and partial epilepsy (with simple or complex symptomatology). This study was undertaken in an attempt to assess the role of the metabolites of carbamazepine, viz. 10, 11-epoxy-carbamazepine and 10, 11-dihydro-10,11-dihydroxy-carbamazepine, with regard to their therapeutic efficacy and the occurrence of side effects of the parent drug. It was also designed to seek a possible explanation as to why certain patients with optimal levels of carbamazepine in plasma fail to respond to therapy. A total of 23 epileptic patients (11 females and 12 males) suffering from either generalised (tonic-clonic) seizures or partial complex seizures took part in the study. The patients were divided into two groups according to their seizure frequency: Responders - those patients who had no seizures in the month prior to entry into the study (12 patients). Non-Responders - those patients who had a minimum of one seizure a week in the month prior to entry into the study (11 patients). Carbamazepine and its metabolites were monitored between 8 a.m. and 6 p.m. by taking blood samples at two hourly intervals. Cerebrospinal fluid (CSF) was also obtained from seven patients in the non-responder group. The drug and its metabolites were assayed simultaneously by the thin-layer chromatographic (TLC) method of Hundt and Clark (1975). Six of the 23 epileptic patients complained of side effects: nausea and headaches were the most frequently mentioned complaint. Statistical analysis showed, however, that there was no significant difference in the peak levels of carbamazepine and metabolites in patients both with or without side effects. Therefore, it was not possible to define a threshold level of the drug above which side effects were likely to occur. Also, no definite conclusion could be reached as to whether the metabolites play a role in the manifestation of side effects. The area under the curve (AUC) is a measure of the overall plasma concentration of carbamazepine and metabolites (present between 8 a.m. and 6 p.m.) in the individual patients of the two groups. There was no significant difference in the AUC of carbamazepine between responders and non-responders. However, the AUC of the dihydroxy and epoxy metabolites was significantly higher in the non-responders (P<-0.002 and P < 0.02 respectively). Moreover, in the CSF samples of the non-responders, the mean (±SD) ratio of the dihydroxy metabolite to the parent drug was as high as 1.17 (±0,36). The results show a clear association between high levels of metabolites and poor response to carbamazepine therapy. Furthermore, it would seem that either both metabolites are inactive or that if the epoxy metabolite is active as in the rat (Frigerio and Morselli 1975), any likely therapeutic effect is counter-acted by the relatively large concentration of inactive dihydroxy metabolite (Schmutz et al 1979). Moreover, it may follow that non-response to carbamazepine - despite optimal levels of the drug in plasma - may be due to competition by inactive dihydroxy metabolite for the site (s) of action of the parent drug in the brain. Research strategies which might be used to test this hypothesis have been proposed.